The relationship between HIV-related stigma and HIV self-management among men who have sex with men: The chain mediating role of social support and self-efficacy - Tao, Yan; Xiao, Xueling; Ma, Jun; Wang, Honghong (Frontiers in Psychology, 2022)
HIV infection becomes a manageable illness, and self-management is one of the key indicators of achieving optimal health outcomes. Men who have sex with men (MSM) living with HIV face many psychosocial challenges when managing HIV infection, such as sexual minority pressure and HIV-related stigma. Higher perceived HIV-related stigma had been related to low self-management. However, the mechanisms underlying the association between HIV-related stigma and HIV self-management are unclear. Two possible mediators include social support and self-efficacy. This study aimed to examine the relationship between HIV-related stigma and HIV self-management among MSM living with HIV and to explore the single mediating effect of social support and self-efficacy and the chain mediating effect of these two variables on this relationship in China. Convenience sampling was used to recruit participants from the Center for Disease Control (CDC) in Changsha City, Hunan province, China. A total of 459 MSM living with HIV completed questionnaires regarding sociodemographic and disease-related information, HIV-related stigma, social support, self-efficacy, and HIV self-management. Descriptive statistics analysis, one-way ANOVA, independent t-tests, pearson’s bivariate correlation and multiple regression were conducted using the SPSS v24.0. Process macro in SPSS was used to analyze the single and chain mediating effect among variables. Our findings showed that the indirect and total effect of HIV-related stigma on HIV self-management was significant, while the direct effect was not statistically significant. Social support and self-efficacy mediated the relationship between HIV-related stigma and HIV self-management, respectively. Moreover, the chain mediating model confirmed that the association between HIV-related stigma and HIV self-management was mediated by social support and self-efficacy sequentially. Future interventions focusing on improving HIV self-management among MSM living with HIV should consider a multi-faced approach.